Perinatal Catatonia in a Patient with a Twin Pregnancy of Unknown Chorionicity and Gestational Age Presenting in Spontaneous Preterm Labor. (12th April 2022) - Farias, Ryan; Hartnett, Janice
Abstract : Catatonia during pregnancy is rare and presents unique challenges due to the potential ramifications to mom and baby of the overall disease state and of potential treatment options. The purpose of this case report is to highlight the complexities in the workup and management of a catatonic patient with concurrent acute obstetric concerns requiring urgent intervention. We report a case of acute catatonia due to underlying major depressive disorder in a patient who presented in spontaneous preterm labor, with a twin pregnancy of unknown chorionicity with no known prenatal care. She underwent an extensive workup with no significant findings on lumbar puncture, brain MRI, metabolic labs, and EEG. After exclusion of several acute underlying conditions, a presumptive diagnosis of catatonia secondary to exacerbation of underlying major depressive disorder was made. She was transferred to an inpatient psychiatric facility postdelivery and treated with a course of lorazepam, aripiprazole, and escitalopram with good effect.